Efeitos transgeracionais dos inseticidas clorantraniliprole e flubendiamida sobre o predador Macrolophus basicornis (Hemiptera: Miridae) - Mesak, Luana (2020)
The tomato moth Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) is one of the main pests that affect tomato plantations around the world. Due to the constant application of pesticides in crops, pest populations have become resistant to several chemical groups. For this reason, the development of new active ingredients has been constantly sought, as well as the use of alternative methods of control for the population regulation of this lepidopteran. The release of species belonging to the Miridae family in protected crops is an effective alternative. Among these, the species Macrolophus basicornis (Stal, 1860) (Hemiptera: Miridae) stands out, a promising controlling agent for T. absoluta in Brazil. However, the release of this predator can be compromised by the incessant spraying of insecticides on crops. Thus, the objective of the present work was to evaluate, through life table studies for two sexes by age and stage of development, the possible transgenerational effects of the insecticides chlorantraniliprole and flubendiamide, commonly used in the control of T. absoluta, to the predator M. basicornis. M. basicornis couples were treated with the insecticides chlorantraniliprole and flubendiamide, in the maximum dosages recommended for the control of T. absoluta, and distilled water as control via Potter tower. Then, they were placed in tomato plants cv. Santa Clara for oviposition. The biological, reproductive and population parameters of the progeny from couples treated with insecticides and control were evaluated based on the theory of a life table for two sexes by age and stage of development (Age-stage, Two-sex, life table). The longevity of females and males and the total life cycle of insects were not reduced by the compounds. The application of flubendiamide in the P1 generation caused a reduction in the number of offspring generated by the F1 generation. The insecticides chlorantraniliprole and flubendiamide did not significantly affect important parameters such as r, λ, and R0. The results indicate that the diamides chlorantraniliprole and fluendiamide can be used in tomato crops for the control of T. absoluta with the presence of M. basicornis, however, with greater attention to the latter, for causing a reduction in the fertility of this predator.